2018
DOI: 10.3390/su10082691
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Managers’ Network Awareness and the Relational Strategic Orientation of their Firms: Findings from Interviews with Polish Managers

Abstract: The ability to cooperate with others in interorganisational dyads and networks is a source of competitive advantage for firms today. However, the question arises as to whether managers are aware of this and implement relational orientation as a strategy in their firms to obtain relational rent. The purpose of this paper is to provide an answer to this question. The research was conducted on 53 companies based in Poland using semi-structured interviews with executives. On one hand, the research results allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 117 publications
(153 reference statements)
0
7
0
Order By: Relevance
“…In particular, since prior studies have considered the positive impact of ethical competency and strategic competency of entrepreneurs on the growth of SMEs (Ahmad, 2007;Ahmad et al, 2010;Kaur and Bains, 2013;Man, 2001;, we predict that network competence may act as a mediator in the relationship between the ethical competency and BG, as well as in the relationship between the strategic competency and BG. Some recent studies have shown the association between the strategic competencies with network competence (Forkmann et al, 2018;Mu et al, 2017;Zakrzewska-Bielawska, 2018). Networks support the small firms in gaining the valuable resources (Yli-Renko et al, 2001) and achieving the survivability and growth by entering in the new markets (Lee et al, 2001).…”
Section: Effect Of Ethical Competencymentioning
confidence: 99%
“…In particular, since prior studies have considered the positive impact of ethical competency and strategic competency of entrepreneurs on the growth of SMEs (Ahmad, 2007;Ahmad et al, 2010;Kaur and Bains, 2013;Man, 2001;, we predict that network competence may act as a mediator in the relationship between the ethical competency and BG, as well as in the relationship between the strategic competency and BG. Some recent studies have shown the association between the strategic competencies with network competence (Forkmann et al, 2018;Mu et al, 2017;Zakrzewska-Bielawska, 2018). Networks support the small firms in gaining the valuable resources (Yli-Renko et al, 2001) and achieving the survivability and growth by entering in the new markets (Lee et al, 2001).…”
Section: Effect Of Ethical Competencymentioning
confidence: 99%
“…An interesting aspect of further research could be an assessment of the role of managers in the cultural context, organization management, and network awareness [62,63]. With regard to environmental issues, an important aspect seems to be industrial symbiosis "which refers to a collaborative strategy of exchanging physical resources and sharing services among industrial actors, which enhances the resource efficiency and reduces the environmental impacts of industrial operations within the network" [64] (p.1).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research is characterized by induction models [34], in which a priori image of reality is not assumed, but research questions are formulated and then generalizations are formulated on the basis of empirical research [35,87]. Qualitative research uses empiricism and induction.…”
Section: Qualitative Research Methodsmentioning
confidence: 99%